2019
DOI: 10.1177/0897190019840100
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional Perceptions and Attitudes Among Pharmacy and Family Nurse Practitioner Students

Abstract: Introduction: Interprofessional education (IPE) activities involving pharmacy (PharmD) and family nurse practitioner (FNP) students is understudied. Interactions between PharmD and FNP students have become important since most recent Accreditation Council for Pharmacy Education standards included a requirement for schools of pharmacy to have IPE. The primary objective of this study is to evaluate the perceptions and attitudes among PharmD and FNP students towards an IPE activity. Methods: Atleast 1 student fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Pharmacogenomic based on this situation, we need to arrange the Interprofessional Education (IPE) started from the undergraduate program in the multidiscipline area. A systematic review of the pharmacy perspectives on IPE found that pharmacy students had a positive attitude about IPE and collaborative practice [6,7]. Even though there was a negative professional stereotype of the IPE, however, some interventions can change into favorable ones [8].…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacogenomic based on this situation, we need to arrange the Interprofessional Education (IPE) started from the undergraduate program in the multidiscipline area. A systematic review of the pharmacy perspectives on IPE found that pharmacy students had a positive attitude about IPE and collaborative practice [6,7]. Even though there was a negative professional stereotype of the IPE, however, some interventions can change into favorable ones [8].…”
Section: Introductionmentioning
confidence: 99%